2017
DOI: 10.18632/oncotarget.22346
|View full text |Cite
|
Sign up to set email alerts
|

Dietary miR-451 protects erythroid cells from oxidative stress via increasing the activity of Foxo3 pathway

Abstract: One fundamental issue in public health is the safety of food products derived from plants and animals. A recent study raised a concern that microRNAs, which widely exist in everyday foods, may alter consumers’ functions. However, some studies have strongly questioned the likelihood of dietary uptake of functional microRNAs in mammals. Here we use a microRNA gene knockout animal model to show that miR-144/451 null mice can orally uptake miR-451 from a daily chow diet, and ingestion of wild type blood, that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…These findings demonstrate that sickle erythrocytes can transfer their enriched miR-451 into parasites to suppress malaria infection. These findings, together with a recent report that dietary miR-451 (presumably from fish powder) is capable of passing through the gastrointestinal system into circulating blood to regulate the erythroid functions of mice [64], support the notion that miRNAs may perform cross-species gene regulation [65].…”
Section: Mir-144/451 In Erythrocyte Development and Red Cell Diseasessupporting
confidence: 69%
See 1 more Smart Citation
“…These findings demonstrate that sickle erythrocytes can transfer their enriched miR-451 into parasites to suppress malaria infection. These findings, together with a recent report that dietary miR-451 (presumably from fish powder) is capable of passing through the gastrointestinal system into circulating blood to regulate the erythroid functions of mice [64], support the notion that miRNAs may perform cross-species gene regulation [65].…”
Section: Mir-144/451 In Erythrocyte Development and Red Cell Diseasessupporting
confidence: 69%
“…Another fundamental issue in miR-144/451 biology is that miR-144/451, especially miR-451, are considered erythroid lineage-specific genes whose expression are mainly limited to within erythrocytes and their precursors; in other words, whether low miR-144/451 expression can alter the path of normal development. A recent report has addressed this question by showing that a trace amount of miR-451 affects the clearance of ROS in red blood cells [64]. In this report, authors show that miR-144/451 gene knockout animals are capable of orally uptaking miR-451 to the blood stream from daily chow diet, presumably from fish powder in the food.…”
Section: Mir-144/451 In Tumorigenesismentioning
confidence: 94%
“… [ 152 ] 2017 Ingestion of wild type blood increased the levels of miR451 and miR144 in peripheral blood of miR144/451-null mice miR451 miR144 Wild type mice blood At very low level but biologically relevant amount Exosomes Exogenous miR451 existing in miR144/451 knockout mice enhanced anti-oxidant activity in vivo via increasing the activity of Foxo3 pathway Two different RT-qPCR, Dual-luciferase reporter assay, WB, FACS miRNAs in foods or dietary supplements could affect the functions of the consumer. [ 153 ] MVs microvesicles, HTS high-throughput sequencing; RT-qPCR quantitative real time polymerase chain reaction, NB Northern blot, WB Western blot, ELISA enzyme-linked immunosorbent assay, FACS Fluorescent activated cell sorting, SOP standard operating procedure, rRNAs ribosomal RNAs, fM femtomole (10 −12 mol/L) …”
Section: Introductionmentioning
confidence: 99%
“…41 We have recently demonstrated that a trace amount of miR-451 could have a big impact on the clearance of reactive oxidative species in red blood cells. 42 These observations indicate that it is not necessary for certain miRNAs to reach high levels to be functional. In the future, it will be interesting to investigate the effects of miR-144 and miR-451 on erythropoiesis F I G U R E 7 Myc directly suppresses the expression of miR-144/451.…”
Section: Discussionmentioning
confidence: 99%